2004
DOI: 10.1177/014572170403000619
|View full text |Cite
|
Sign up to set email alerts
|

Family Support, Diet, and Exercise Among Older Mexican Americans With Type 2 Diabetes

Abstract: Family behavior is associated with diet and exercise self-care. Diabetes educators and healthcare providers should consider involving the entire family in the management of older patients with type 2 diabetes. Interventions designed to improve diabetes self-management should address family support specific to diabetes, self-efficacy, and barriers to self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
237
4
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(275 citation statements)
references
References 34 publications
24
237
4
10
Order By: Relevance
“…Family environment also appears to significantly affect compliance (8,9) . As eating patterns are likely to be similar across family members (10,11) , adherence and maintenance of certain eating patterns might be associated with the level of household support for healthy eating (8,9) . A combined worksite and family intervention is more successful in changing nutritional patterns than worksite intervention alone (12)(13)(14) .…”
mentioning
confidence: 99%
“…Family environment also appears to significantly affect compliance (8,9) . As eating patterns are likely to be similar across family members (10,11) , adherence and maintenance of certain eating patterns might be associated with the level of household support for healthy eating (8,9) . A combined worksite and family intervention is more successful in changing nutritional patterns than worksite intervention alone (12)(13)(14) .…”
mentioning
confidence: 99%
“…El apoyo familiar vinculado a la alimentación ha sido demostrado por Epple y cols., en nativos Navajos con DM2, donde el apoyo familiar activo se asoció significativamente con el control de triglicéridos, colesterol y la disminución en los puntos porcentuales de la HbA 1c 2004 encontraron una asociación entre el apoyo familiar y el autocuidado, específicamente en la adherencia a la dieta y ejercicio en sujetos México americanos con DM2 27 . De manera más reciente, Watanabe y cols., en 2010 identificaron al apoyo familiar como un componente crucial para el logro del control glicémico; su estudio mostró que los pacientes con DM2 con apoyo familiar en el área de nutrición mejoraron los niveles de HbA 1c y triglicéridos 28 .…”
Section: Discussionunclassified
“…For example, the role of the family in providing support was reported in two recent systematic reviews, which showed that involvement of family members as facilitators was beneficial in helping those with chronic disease to maintain a positive approach to self-management, such as physical activity, diet, and medication (Schulman-Green et al, 2016;Whitehead, Jacob, Towell, Abu-Qamar, & Cole-Heath, 2017). People with higher family support levels, which can lead to higher confidence levels, seem to have better disease management (Rosland et al, 2008;Stamp et al, 2016;Wen, Parchman, & Shepherd, 2004). It could be because the family provides extra support in caring for people with illness, particularly for those with chronic disease and needing regular follow-up.…”
Section: 21mentioning
confidence: 99%